Benthos response to nutrient enrichment and functional consequences in coastal ecosystems. (March 2022) - Pascal, Ludovic; Chaillou, Gwénaëlle; Nozais, Christian; Cool, Joannie; Bernatchez, Pascal; Letourneux, Kevin; Archambault, Philippe
Abstract: As land use intensifies, many coastal waters are becoming enriched with otherwise limiting nutrients, leading to eutrophication. While the extreme effects of eutrophication on benthic communities are well documented, there is still a lack of knowledge about how nutrient enrichment alters biogeochemical interactions occurring at the sediment-water interface. Using ex-situ experiments, this study explores the consequences of nutrient enrichment on sediment characteristics, macrofauna community and benthic fluxes. The quantity of sedimentary organic matter and porewater concentration of NH4 +, NOx and PO4 3− increased in enriched treatments. These changes did not affect the macrobenthic community structure. However, macroinfauna buried less deep and increased their ventilation activity. As consequences, nutrient efflux increased, thereby favouring eutrophication processes. These effects were reduced in presence of seagrass, thus illustrating the buffering capacity of seagrass in the context of environmental changes, and particularly, of eutrophication. Overall, this study highlights that the functional consequences of nutrient enrichment involve interconnected processes that are variable in space and time. Graphical abstract: Image 1 Highlights: Ex-situ experiment studying effects of fertilisation on benthic compartment. Fertilisation increased organic matter content at the sediment surface. Fertilisation increased the concentration of reduced chemical species in porewater. Fertilisation reduced the penetration depth of macroinfauna. In enriched treatments, sediment became a source of nutrients for the water column.